Strategi Membangun Brand Dalam Meningkatkan Keunggulan Bersaing Produk UMKM Coklat Cho Jaensan di Kabupaten Jembrana - Sulistyawati, Ni Kadek Krisna (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
This research is motivated by the phenomenon of Competitive Advantage (Y) in Cho Jaensan's chocolate MSME products in Jembrana Regency. The purpose of this study is to analyze and prove the influence of Line Extension (X1), Brand Extension (X2), and New Brand (X3) on Competitive Advantage (Y) of Cho Jaensan's chocolate products. This study adopts a quantitative research approach and employs purposive sampling, involving 110 respondents. Data analysis was conducted using multiple linear regression with SPSS version 26. The resulting regression equation is: Y = 2.772 + 0.695X1 + 0.725X2 + 0.640X3. The findings indicate that: First, Line Extension has a positive influence on Competitive Advantage. Second, Brand Extension also has a positive influence on Competitive Advantage. Third, the New Brand strategy positively affects the Competitive Advantage of Cho Jaensan’s chocolate MSME products in Jembrana Regency. These results suggest that product development strategies through line and brand diversification significantly enhance market competitiveness.